Analisis Pemikiran Childfree Dalam Perspektif Qiyas: Studi Kritis Terhadap Keputusan Tidak Memiliki Anak - Muhammad Ajiseftian Suryatama; Syarifuddin (Kartika: Jurnal Studi Keislaman, 2025)
This study critically examines the contemporary phenomenon of childfree through the perspective of Islamic legal reasoning, particularly the method of qiyas (analogical deduction). In modern discourse, the decision to remain childfree is often regarded as an individual right and a matter of personal autonomy. However, within the framework of Islamic law, marriage is not solely a personal contract but also a social and religious institution that upholds the objectives of the maqashid shari’ah, one of which is the preservation of lineage (hifzh al-nasl). This research draws an analogy between the childfree lifestyle and classical Islamic practices such as ‘azl (coitus interruptus) and contraception, while analyzing their similarities and differences. Using a normative qualitative approach, the study evaluates the implications of childfree on the fulfillment of spousal rights and the realization of the essential purposes of marriage. The findings indicate that a permanent choice to remain childfree, if made unilaterally and without mutual consent, risks neglecting core marital objectives and disrupting the balance of rights and obligations between spouses. Therefore, adopting a childfree lifestyle within an Islamic framework requires mutual agreement, comprehensive understanding, and careful consideration of its legal, ethical, and social consequences.